Multiuser-scheduling and resource allocation using max-min technique in wireless powered communication networks - Richu Mary Thomas; Malarvizhi Subramani (Institute of Advanced Engineering and Science, 2022)
Wireless powered communication network (WPCN) is a promising research area for improving network security and speed. The transmission power of the source during the uplink functions as a random variable in WPCN due to the intrinsic power transfer process, whereas it is a constant in typical cooperative networks, culminating in the signal to noise ratio of the source-access point and all the source-relay-access point being mutually correlated. As a result of the massive increase in communication devices powered by battery, the goal of prolonging their life is critical. To get the most throughput in the shortest amount of time, the best uplink and downlink time allocations were calculated. For high throughput and secrecy performance, the proportional max-min fairness algorithm was used in this paper for secure communication in hybrid relays integrated with WPCN. This method allows for multi-user scheduling with optimum targets to provide reliable hybrid outage probability, secrecy outage probability, and energy outage probability. Efficacy of the proposed system was demonstrated regarding throughput, outage probability, and confidentiality. The performance of the model was compared to that of various energy harvesting models like random user scheduling, best user scheduling, and several others, and was found to outperform them for secure transmission.